2008
DOI: 10.1016/j.vetmic.2007.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus phocae, an emerging pathogen for salmonid culture

Abstract: This work describes the characterization of the causal agent of disease outbreaks that, from 1999, occurred repeatedly during the summer months (temperatures higher than 15 degrees C) in Atlantic salmon (Salmo salar) cage-farmed in Chile affecting both smolts and adult fish cultured in estuary and marine waters, reaching in some occasions a cumulative mortality up to 25% of the affected population. Diseased fish showed exophthalmia with accumulation of purulent and haemorrhagic fluid around eyes, and ventral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 21 publications
3
65
1
Order By: Relevance
“…The morphological, physiological and biochemical characteristics useful in the identification of S. phocae have been detailed by several authors (Skaar et al, 1994;Gibello et al, 2005;Romalde et al, 2008). These phenotypic results indicated that S. phocae constitutes a homogeneous taxon with typical characteristics useful for the identification of this pathogen.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The morphological, physiological and biochemical characteristics useful in the identification of S. phocae have been detailed by several authors (Skaar et al, 1994;Gibello et al, 2005;Romalde et al, 2008). These phenotypic results indicated that S. phocae constitutes a homogeneous taxon with typical characteristics useful for the identification of this pathogen.…”
mentioning
confidence: 95%
“…These phenotypic results indicated that S. phocae constitutes a homogeneous taxon with typical characteristics useful for the identification of this pathogen. However, serological studies demonstrated antigenic heterogeneity within this species, with the seal isolates classified into Lancefield's serogroups F and, in a much minor extent, C or untypable (Skaar et al, 1994;Vandamme et al, 1997), and the salmon isolates into serogroup G (Romalde et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcosis is an economically important disease that has been reported in over 30 farmed fresh and saltwater fish species including catfish (Shewmaker et al 2007), tilapia (Eldar et al 1995), trout (Hoshina et al 1958, Eldar et al 1995, salmon (Romalde et al 2008), red drum (Eldar et al 1999), flounder (Baeck et al 2006), yellowtail (Kusuda et al 1991), hybrid striped bass (Evans et al 2000) and turbot (Toranzo et al 1994). The occurrence of streptococcosis in fish appears to be stress related with low grade chronic mortalities seen in some fish species and acute mortalities of 30 to 50% occurring in others as a result of an encephalitis and/or systemic infection affecting multiple organs (Eldar et al 1995, Ringo & Gattesoup 1998, Camus et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Besides its disinfecting inTRODuCTiOn Fish diseases of major importance in Chilean salmon farming includes infectious pancreatic necrosis (iPn) and Piscirickettsia salmonis (Fryer and Hedrick 2003), which cause significant economic losses due to mortalities of atlantic salmon, Salmo salar, fry and post-smolt in seawater. in addition, an increase in disease detection of emergent pathogens as Vibrio ordalii (Colquhoum et al 2004), Streptococcus phocae (Gibello et al 2005, Romalde et al 2008, Francisella (Birkbeck et al 2007) and, lately, Vibrio anguillarum (avendaño-Herrera et al 2007) has been observed in the last decade. To date, economic losses caused by these bacterial pathogens, except V. ordalii, have decreased; however, it remains one of the properties, few studies have been designed to assess the quaternary ammonium compounds, particularly a synergistic blend of superquats and glutaraldehyde (Duplalim ® , Veterquímica S.a., Chile), which is commercialized as a disinfectant of broad spectrum, presenting fast action and low toxicity.…”
mentioning
confidence: 99%